Valeriana umbellifera (Caprifoliaceae): a new saxicolous endemic taxon from Central Chile mountains - Cádiz-Véliz Arón; García Nicolás; Villarroel, Alejandro E.; Zúñiga-Acevedo, Paula (Phytotaxa, 2026)
Valeriana, comprissing approximately 436 species, represents a successful evolutionary radiation within Dipsacales, with an important center of diversification in South America. In Chile, 46 species are currently recognized, 41.3% of which are endemic; two are reported as Endangered and one is probably extinct. The genus is mainly represented by herbaceous species, a calyx that is entire or modified into a pappus, a gamopetalous and pentamerous corolla, an inferior ovary, and an achene as indehiscent dry fruit. During botanical surveys in mountainous areas of Central Chile, specimens of a Valeriana restricted to crevices of steep rocky walls were found. Examination of herbarium material and relevant literature confirmed that it corresponds to a previously undescribed species, here named Valeriana umbellifera. This taxon is characterized by its perennial herbaceous habit, strictly saxicolous ecology, fleshy and glossy leaves arranged in a rosette, and a capituliform inflorescence with an umbel-like appearance. Its phylogenetic position was evaluated using molecular markers within the framework of previous analyses of Valeriana species from the southern Andes. According to IUCN criteria, we propose that the species be categorized as Endangered (EN) due to its restricted distribution, fragmented populations, and threats. The restricted distribution and ecological specialization of this new species underscore the conservation importance of rocky microhabitats in Central Chile, which are increasingly threatened by human activities.